Pencegahan dan Penanganan Skabies di Desa Pulopancikan, Gresik - Tiara Prima Ninting Novansca; Agung Anjar Sukmantoro; Widhi Nastiti; Viera Permatasari Wiana; Diana Rahman; Iqhro’ Samudro Thirto Buono; Khresno Bhirowo Ghusti Buono; Siti Hafida Nur Hidayati; Wijayaningrum Wijayaningrum; Aguslina Kirtishanti; Eko Setiawan; Ika Mulyono Putri Wibowo; Astrid Pratidina Susilo (Universitas Muhammadiyah Surakarta, 2024)
Scabies is a contagious skin disease with a predisposition to people who live in densely populated areas. Pulopancikan Village has the highest prevalence of scabies among other villages in Gresik, East Java. From the results of a survey of visits to the homes of Pulopancikan Village residents, it was concluded that the high level of scabies transmission in the village occurred due to a lack of public knowledge about the disease, especially in terms of prevention and treatment. The aim of this program is to intervene in the form of community education, creating educational feedback sheets, and distributing checklists for preventing and treating scabies at home. This intervention is aimed at mothers or families who have children with scabies health problems. Knowledge tests were carried out before and after the intervention to evaluate the project, which showed a significant difference in increasing the knowledge of the Pulopancikan Village community (p<0.05). However, in this program, the long-term impact of increasing this knowledge cannot yet be known. Therefore, it is necessary to carry out long-term investigations to see the impact of interventions on behavior change, including prevention and regularity of therapy, and reducing the prevalence of scabies. To prevent further transmission, adequate health education must begin when the patient is diagnosed with scabies at the Community Health Center, involving an interprofessional team such as doctors and pharmacists.